Photostability and photostabilizing effect of humic acids. (2000) - Mekkaoui, M.; Elazzouzi, M.; Bouhaouss, A.; Ferhat, M.; Chovelon, J. M.; Meallier, P.
Abstract : The photolysis of Humic Acids (HA) extracted from Moroccan soil in water under simulated sunlight method has been studied. The photochemical degradation of HA in concentration (30 mg/L) has been followed by TOC (Total Organic Carbon) and E4/E6 ratio (The E4/E6 value widely used to characterize humic acids is the ratio of absorption intensities at 465 and 665 nm). HA were found photostable after 24 h of irradiation exposure and produce a screen effect on photochemical degradation of TRB (Tribenuron-methyl) and IMAZ (Imazapyr) herbicides.